Community perception of biocontrol agent using Betta splendens (Ikan Cupang) against Aedes aegypti larvae: a community study in Bali - Sudiartawan, I Putu; Erjana , I Gede Putra; Juliasih , Ni Ketut Ayu; Arsana , I Nyoman (Universitas Gadjah Mada, 2023)
Purpose: This study attempted to analyze the predation ability of Betta splendens as a biocontrol of Aedes aegypti larvae with a case study in Kartika Neighborhood, Dauh Puri, Denpasar City. Methods: This study employed a quasi-experimental approach and a qualitative investigation to ascertain public perceptions of using Betta splendens as a biocontrol agent for Aedes aegypti larvae. The trial lasted one month. Betta splendens were added to the respondent's bath (n=30), and larval mortality was determined at 2, 4, 6, 8, and 10 hours. Analysis of data using the paired t-test. Results: The results showed that the characteristics of respondents were dominated by being 18–45 years old (73.30%), being male (56.70%), having a dominant education level of high school (66.60%), and using a cement bathtub (53.30%). The comparative test results obtained a p-value of 0.0001 (p<0.05), indicating a very significant change in the number of Aedes aegypti larvae during bathing before and after adding Betta fish, with an average predation ability of 85.87%. Community perception regarding using Betta fish as a biocontrol agent is very positive, and the acceptance rate and sustainability of Betta fish use reached 96.67%. There is no change in water conditions due to aroma, color, and taste. Conclusion: The predation power of Betta splendens as a natural biocontrol is excellent and effectively utilized in minimizing the presence of Aedes aegypti larvae in the bath (container).